Do MRPS18-2 and RB proteins cooperate to control cell stemness and differentiation, preventing cancer development? - Kashuba, E.; Mushtaq, M. (Experimental Oncology, 2017)
In childhood tumors, including retinoblastoma, osteosarcoma, and neuroblastoma, the RB-E2F1 pathway is inactivated, as a rule. These tumors arise from precursor cells that fail to undergo the terminal differentiation. Noteworthy, the RB1-encoded protein (RB) does not control the cell cycle in embryonic stem cells. It has not been yet well understood how RB controls cell stemness and differentiation. The question arises why “inactive” RB is required for the survival and stemness of cells? Recently, we have found that overexpression of the RB-binding protein MRPS18-2 (S18-2) in primary fibroblasts leads to their immortalization, which is accompanied by the induction of embryonic stem cell markers and, eventually, malignant transformation. We suggest that cell stemness may be associated with high expression levels of both proteins, RB and S18-2. There must be a strict regulation of the expression levels of S18-2 and RB during embryogenesis. Disturbances in the expression of these proteins would lead to the abnormalities in development. We think that the S18-2 protein, together with the RB, plays a crucial role in the control on cell stemness and differentiation. We hope to uncover the new mechanisms of the cell fate determination. The S18-2 may serve as a new target for anticancer medicines, which will help to improve human health.